2022
DOI: 10.1097/pts.0000000000000976
|View full text |Cite
|
Sign up to set email alerts
|

Use of Hospital Capacity Command Centers to Improve Patient Flow and Safety: A Scoping Review

Abstract: ObjectivesDelayed emergency department (ED) and hospital patient throughput is recognized as a critical threat to patient safety. Increasingly, hospitals are investing significantly in deploying command centers, long used in airlines and the military, to proactively manage hospital-wide patient flow. This scoping review characterizes the evidence related to hospital capacity command centers (CCCs) and synthesizes current data regarding their implementation.MethodsAs no consensus definition exists for CCCs, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Active bed management can decrease the length of stay for boarding patients in the ED. A recent scoping review suggested that capacity command centers, responsible for the bed management of a specific healthcare facility or system, could improve patient flow and safety, thus reducing ED boarding [50 ▪ ]. The implementation of a centralized coordination center to systematically coordinate emergency transfers was associated with a reduction in the ED LOS [51 ▪ ].…”
Section: Hospital Solutionsmentioning
confidence: 99%
“…Active bed management can decrease the length of stay for boarding patients in the ED. A recent scoping review suggested that capacity command centers, responsible for the bed management of a specific healthcare facility or system, could improve patient flow and safety, thus reducing ED boarding [50 ▪ ]. The implementation of a centralized coordination center to systematically coordinate emergency transfers was associated with a reduction in the ED LOS [51 ▪ ].…”
Section: Hospital Solutionsmentioning
confidence: 99%
“…In 2019, the hospital opened a formal capacity center, physically combining the functions of admitting, bed management, hospital transfers, ED transfers, and capacity management, serving as the new home of the MOD. [8][9][10] This allowed for daily collaboration on capacity challenges and transfer priorities.…”
Section: History and Developmentmentioning
confidence: 99%
“…[8][9][10] Although command centers are widely used in traditional hospital settings for optimizing patient throughput, effectiveness of HaH command centers is unclear, particularly for patient enrollment. 11 It has not been described if HaH patient enrollment is best performed by a centralized command center or by local healthcare team members. and bedside registered nurses (RN) located in a remote command center.…”
Section: Introductionmentioning
confidence: 99%